Clinical and ultrasound assessment of body composition in preterm infants at discharge: an observational study - Beatriz del Rey Hurtado de Mendoza; Montserrat Izquierdo Renau; Elsa García González; Carla Balcells-Esponera; Emilio J Inarejos Clemente; Isabel Iglesias-Platas (BMJ Paediatrics Open, 2025)
Objectives While the target of growth of very preterm infants (VPIs) during Neonatal Intensive care unit (NICU) admission is still controversial, the most accepted objective is that they should follow their intrauterine trajectory in terms of growth and body composition (BC). BC is difficult to measure in clinical daily routine but proxies like body ratios and skinfolds have been used. Prenatal and postnatal factors can influence the growth and BC of VPIs in the NICU.Design, setting and patients We conducted a case-control study, including preterm infants born before 32 weeks gestational age at term-corrected age (TCA) and healthy late preterm or term infants as controls and also a retrospective cohort analysis of factors influencing VPI’s BC at discharge. Patients had an anthropometric evaluation at discharge including weight, length, head circumference, body circumferences (waist, arm), skinfolds and abdominal ultrasound (US).Results 191 VPIs were eligible for discharge visits, but only 83 had a complete evaluation and we collected 26 controls. VPIs at TCA were smaller in weight, length and head circumference but had greater ratios (arm fat-to-circumference and waist-to-length). Abdominal fat assessed by US was smaller in VPIs compared with term infants. Intrauterine growth restriction-VPI remained smaller at TCA but experienced less weight z-score loss. Sex did not seem to influence growth and BC proxies at TCA. Higher nutritional support during the first 2 weeks of life was related to a lower loss of length z-scores, and exclusive human milk feeding correlates with arm fat-to-circumference ratio.Conclusions Growth and BC of VPIs can be approached using simpler measures in clinical practice. Arm skinfolds and arm circumferences point to a greater adiposity of VPIs at TCA compared with term infants, while US does not show a greater visceral adiposity. Nutritional factors played a small effect in BC at the time of discharge.